2018
DOI: 10.1101/371443
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the impact of competing intra- and intermolecular triplet-state quenching on photobleaching and photoswitching kinetics of organic fluorophores

Abstract: Abstract:While buffer cocktails remain the gold-standard for photostabilization and photoswitching of fluorescent markers, intramolecular triplet-state quenchers emerge as an alternative strategy to impart fluorophores with 'self-healing' or even functional properties such as photoswitching. In this contribution, we evaluated various combinations of both approaches and show that inter-and intramolecular triplet-state quenching processes compete with each other rather than being additive or even synergistic. Of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 69 publications
(104 reference statements)
6
20
0
Order By: Relevance
“…It has to be stressed out that the time-point where signal-loss occurs (see Figure 5a, where the signal abruptly decreases to background level) might reflect either irreversible photobleaching or UV-reversible off-switching. In line with our previous work we refer to this as "apparent photobleaching lifetime" 44 , which reflects both pathways for fluorescence deactivation.…”
Section: Photostabilizer-dye Conjugates For Localization-based Storm supporting
confidence: 81%
See 4 more Smart Citations
“…It has to be stressed out that the time-point where signal-loss occurs (see Figure 5a, where the signal abruptly decreases to background level) might reflect either irreversible photobleaching or UV-reversible off-switching. In line with our previous work we refer to this as "apparent photobleaching lifetime" 44 , which reflects both pathways for fluorescence deactivation.…”
Section: Photostabilizer-dye Conjugates For Localization-based Storm supporting
confidence: 81%
“…Related to this requirement, our group recently reported the effects of intramolecular photostabilizers on the action of solution-based additives such as Trolox, COT, TCEP and cysteamine (MEA). 44 In that paper, we evaluated the competition between inter-and intramolecular triplet-state quenching processes and showed that those are neither additive nor synergistic. Our findings revealed that intramolecular processes dominate the photophysical properties of different organic fluorophores for combinations of covalentlylinked and solution-based photostabilizers and importantly also photoswitching agents used for STORM.…”
Section: Photostabilizer-dye Conjugates For Localization-based Storm mentioning
confidence: 99%
See 3 more Smart Citations